Needs Analysis for the Development of E-Student Worksheets for the PBL Model Based on PhET Simulations Oriented to Local Wisdom to Improve Students' Problem-Solving Skills for Fluid Material - Mazra Atur Rifka; Hidayati Hidayati; Fatni Mufit; Selma Riyasni (Jurnal Penelitian Pembelajaran Fisika, 2026)
Physics plays an important role in developing problem-solving skills as a 21st-century learning demand. However, in fluid materials, this ability is still low due to difficulties in understanding abstract concepts and the limited use of interactive media. This research aims to determine the initial problem-solving ability and the need for the development of teaching materials. The study used a descriptive approach in the form of a preliminary study at MAN 3 Padang City in class XI Science 2 with 26 students. Data was collected through tests, interviews, and questionnaires, then analyzed descriptively. The results showed that 53.8% of students were in the category of failure, 3.8% lacking, 15.4% adequate, 15.4% good, and 11.5% very good, so problem-solving skills are still low. In addition, students have good technological readiness, but have not been supported by adequate learning media. Therefore, it is necessary to develop E-LKPD based on Problem-Based Learning (PBL) supported by PhET Interactive Simulations simulations and oriented to local wisdom to improve students' understanding of concepts and problem-solving skills.